(untitled) - Chopra, V. L. (New York, 2005)
A handy guide on crops of international importance. The Handbook of Industrial Crops is a comprehensive exploration of 12 important agricultural components of economy and export trade. The book examines the aspects of cultivation and trade in addition to the available information on the evolution and adaptation of each agricultural crop. With this extensive resource, you get detailed, up-to-date information on each species’ origin and botany, cultivation and harvest, and prospective future of available production and demand to set you up for higher production and sales
Keywords: Crops,Botany, economic,Produce trade; Handbooks, manuals, etc.,Handbooks, manual, etc,Handbooks, manuals, etc